A note on Euclidean spaces R^n and n-normed spaces - Idris, Mochammad (KOMUNITAS Analisis Matematika INDONESIA, 2023)
This article gives us a relation between Euclidean space R^n and a subspace of X (an n-normed space) using properties of determinant of square matrices. Some functionals will be investigated on these spaces. Furthermore, we obtain definition of inner product and m-inner product with m<n on the subspace of X.